Produção e qualidade do leite e da manteiga de vacas alimentadas com grãos de linhaça e monensina sódica - Silva, Daniele Cristina da (2006)
The aim of this trial was to evaluate the effect of feeding ground flaxseed and monensin in the parameters: intake and digestibility of nutrients; milk production, composition and quality; butter fatty acid profile and composition of blood. Eight Holstein cows with average body weight of 570 + 43 kg were assigned in a double latin square design with 4 experimental periods of 21 days each. The treatments were: whole flaxseed without monensin (WFNM), whole flaxseed with monensin (WFWM), ground flaxseed without monensin (GFNM) and ground flaxseed with monensin (GFWM). Dry matter (DM) and cruden protein (CP) intake, apparent digestility of DM, CP, organic matter (OM), ether extract (EE), neutral detergent fiber (NDF), acid detergent fiber (ADF) and nonstructural carbohydrates (NEC) were estimated. Evaluations of milk production and yield of 3.5% fat-corrected milk (FCM), pH, density, protein, fat, lactose, total solids, urea nitrogen, somatic cell score (SCS) and fatty acid profile of milk were also performed. Blood was sampled with animals in starvation to determine glucose, triglycerides, total cholesterol, HDL, LDL and VLDL. The butter produced with the milk cream was used to determine fatty acid profile and contents of fat, DM and pH. Cows fed whole or ground flaxseed with or without monensin showed similar DM and CP intake. However, ground flaxseed improved EE and CP digestibility and decreased ADF digestibility. Yield of 3.5%FCM, milk fat and saturated fatty acids were decreased with monensin addition. Ground flaxseed provided more polyunsaturated fatty acids (PUFA) and omega-3 in both milk and butter. However, this treatment also promoted greater levels of milk urea nitrogen (MUN). Cows fed ground flaxseed or diet without monensin had greater omega-6/omega-3 ratio in milk and butter than those animals fed whole flaxseed or monensin. On the other hand, monensin provided CLA (Conjugated Linoleic Acid) to milk and butter and decreased saturated fatty acids, although it increased LDL in blood. Ground flaxseed is more satisfactory than whole flaxseed for most of the evaluated parameters.